PENGARUH PEMBERIAN EDUKASI ONLINE TENTANG PELAYANAN IMUNISASI DIMASA PANDEMIC COVID-19 DENGAN PENGETAHUAN DAN SIKAP IBU UNTUK KUNJUNGAN BALITA KE POSYANDU DI WILAYAH KERJA PUSKESMAS TANJUNG LANGKAT TAHUN 2021 - Putri Ayu Yessy Ariescha (Jurnal Inovasi Kesehatan Masyarakat, 2022)
In times of a pandemic like today, people hope that vaccines will be available soon and experts around the world seem to be competing to find a vaccine. But of course the vaccine development process takes a long time. On the other hand, when the burden of diseases that can be prevented by immunization has begun to decrease, people often forget or even avoid the immunization program. A number of parents are worried about providing immunizations for their children, and not a few health workers are hesitant in providing immunization services in the midst of the COVID-19 pandemic. The purpose of this study was to analyze the effect of providing online education about immunization services during the Covid-19 pandemic with the knowledge and attitudes of immunization mothers and for toddler visits to posyandu in the Tanjung Langkat Health Center work area. This study uses a quasi-experimental research design that is one group pretest posttest. The number of samples in this study were 42 respondents. The results of the study based on the Mc.Nemar statistical test, it was known that there was an effect of providing online education about immunization services during the Covid-19 pandemic with the knowledge and attitude of immunization mothers and for visits to the Posyandu in the Tanjung Langkat Health Center working area with a P Value of 0.000.